2012
DOI: 10.3233/wor-2012-0797-5057
|View full text |Cite
|
Sign up to set email alerts
|

The use of affective interaction design in car user interfaces

Abstract: Recent developments in the car industry have put Human Machine Interfaces under the spotlight. Developing gratifying human-car interactions has become one of the more prominent areas that car manufacturers want to invest in. However, concepts like emotional design remain foreign to the industry. In this study 12 experts on the field of automobile HMI design were interviewed in order to investigate their needs and opinions of emotional design. Results show that emotional design has yet to be introduced for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the existing research in academic circle, Francois et al [32] and other scholars' framework based on cognitive ergo-nomics verifies the potential benefits of drivers' participation in automotive HMI design. In addition, Gkouskos et al [33] found that sentimental design has not been fully applied to the filed of HMI design through expert interviews. At the same time, with the emergency of applications programs and new features in HMI, the increase of information has a significantly negative impact on drivers' safety [34].…”
Section: A the Application Of Ke In Hmi Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing research in academic circle, Francois et al [32] and other scholars' framework based on cognitive ergo-nomics verifies the potential benefits of drivers' participation in automotive HMI design. In addition, Gkouskos et al [33] found that sentimental design has not been fully applied to the filed of HMI design through expert interviews. At the same time, with the emergency of applications programs and new features in HMI, the increase of information has a significantly negative impact on drivers' safety [34].…”
Section: A the Application Of Ke In Hmi Designmentioning
confidence: 99%
“…Firstly, the data in the table are divided into equivalence classes according to conditional attributes (design characteristics) and decision attributes (elderly-oriented satisfaction). (1,3,13,15,19,21,23,24,31,33,39,43,45,49,53,54,55,58,59), (2,4,5,6,8,10,14,17,20,22,26,28,29,30,32,34,35,36,37,38,42,46,50,51,52,56,57), (7,9,11,12,16,…”
Section: Figure 5 From Deconstruction Tablementioning
confidence: 99%
“…The automotive industry has long been among the sectors that best-understands the importance of drivers' affect and is making much effort to incorporate the affective attributes in their product (Schütte and Eklund, 2005;Chang et al, 2006;Khalid et al, 2012;Helander et al, 2013). To date, affective design studies in the automotive sector have emphasized 'appearance' or 'visceral' aspects such as colour, texture, and shape of exterior (Suzianti et al, 2016) and interior (Leder and Carbon 2005;Ersal et al, 2011;Gkouskos and Fang, 2012) design. As the Advanced Driver Assistance System (ADAS) gets installed in the vehicle, however, the factors affecting the driver's emotion are expanding beyond the appearance to the entire run.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the proliferation of automobiles in society over the past 100 years and the recognition that these once utilitarian, industrial machines are now interwoven into daily lives and personal identities, automotive designers are still at a loss as to how to effectively incorporate elements of emotional design into the total design process [20]. And the problem is not isolated to automobiles.…”
Section: Discussionmentioning
confidence: 99%
“…Since the car experience includes all possible "cognitive processing and affective responses," then cars not only meet transportation needs and aesthetic pleasure but also serve as a status symbol and significantly frame certain social interactions [19]. Engineers cannot account for all these considerations with engineering requirement alone and point out that even with awareness of emotional design components, they lack the tools to apply those components into the design and manufacturing process [20]. Personas address this gap and offer a solution to all fields of engineering and abbreviated personas specifically introduce engineers to this concept during the education process.…”
Section: Background and Literature Reviewmentioning
confidence: 99%